Ex 5.1, 6 In the following figure, if AC = BD, then prove that AB = CD. AC = BD AC = AB + BC BD = BC + CD Substituting for AC and BD from (2) and (3) in (1) , we get AB + BC = BC + CD AB = CD Hence proved

Ask a doubt
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 14 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.